ANALISIS PERAN GURU DALAM MENGEMBANGKAN KECERDASAN MORAL SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANERAAN DI SMP NEGERI 2 HILIMEGAI TAHUN PEMBELAJARAN 2020/2021 - Petrus Fetero Laia (LPPM Universitas Nias Raya, 2022)
This research is motivated by the low moral intelligence of students in Pancasila and citizenship education subjects. The research aims to find out how the teacher's role in developing students 'moral intelligence in Pancasila and citizenship education subjects. The research method uses descriptive research using a qualitative approach. Data collection techniques are observations, interviews, documentation, interviews, documentation, and combinations in the field by noting what the teacher’s role was in developing student’s moral intelligence in Pancasila and citizenship education subjects. Provide moral guidance and be a good role model to students both at school and outside of school. Ilimegai really gives encouragement to students so that students remain enthusiastic in good behavior and learning. Suggestions, 1) Teachers are expected to be able to educate students' morals by being an example in good things, 2) Teachers are expected to pay more attention to the moral intelligence of students in the school environment and outside the school. 3) Teachers are expected to continue to cooperate with students' parents in improving students' moral intelligence.